Control Aspects of the Interzonal Exchange of automatic Frequency Restoration Reserves. Issue 9 (2022) - Maucher, Philipp; Remppis, Simon; Schlipf, Dominik; Lens, Hendrik
Abstract: This paper compares two control methods for the interzonal exchange of automated Frequency Restoration Reserves (aFRR), i.e. their exchange between different control areas (CA), which is mandated by the EU Commission for the future. The Control Demand Model (CDM) was developed for aFRR-exchange between German CA and is the currently implemented model for the European aFRR exchange. In the CDM, the aFRR demand of the CA is optimized, which has the advantage that there is no intervention in the aFRR control loops and therefore stability is guaranteed to be preserved. However, the activation of aFRR is not optimal, since the optimization result and the actual activation differ dynamically due to the aFRR controller of the respective CA. The Control Request Model (CRM) tries to eliminate this disadvantage by placing the optimizer between the controller and the activation. However, this causes the different aFRR control loops to be partially coupled, meaning that stability might be lost without adequate countermeasures. We describe both the CDM and the CRM, including an adaptation for stable operation for the latter. They are then compared using different scenarios. Finally, a stability analysis is carried out for the CRM.